Anti-Proliferative Activity of A Hydrophilic Extract of Manna from Fraxinus angustifolia Vahl through Mitochondrial Pathway-Mediated Apoptosis and Cell Cycle Arrest in Human Colon Cancer Cells - Ignazio Restivo; Luisa Tesoriere; Anna Frazzitta; Maria Antonia Livrea; Alessandro Attanzio; Mario Allegra (Molecules, 2020)
Manna is produced from the spontaneous solidification of the sap of some Fraxinus species, and, owing its content in mannitol, is used in medicine as a mild laxative. Manna is also a rich source of characteristic bio-phenols with reducing, antioxidant and anti-inflammatory properties. This study assesses the activity of a hydrophilic extract of manna (HME) on cellular and molecular events in human colon-rectal cancer cells. HME showed a time- and concentration-dependent anti-proliferative activity, measured by MTT assay, in all the cell lines examined, namely Caco-2, HCT-116 and HT-29. The amounts of HME that caused 50% of cell death after a 24 h treatment were 8.51 ± 0.77, 10.73 ± 1.22 and 28.92 ± 1.99 mg manna equivalents/mL, respectively; no toxicity was observed in normally differentiated Caco-2 intestinal cells. Hydroxytyrosol, a component of HME known for its cytotoxic effects on colon cancer cells, was ineffective, at least at the concentration occurring in the extract. Through flow-cytometric techniques and Western blot analysis, we show that HME treatment causes apoptosis, assessed by phosphatidylserine exposure, as well as a loss of mitochondrial membrane potential, an intracellular formation of reactive oxygen species (ROS), increases in the levels of cleaved PARP-1, caspase 3 and Bax, and a decrease in Bcl-2 expression. Moreover, HME interferes with cell cycle progression, with a block at the G1/S transition. In conclusion, the phytocomplex extracted from manna exerts an anti-proliferative activity on human colon cancer cells through the activation of mitochondrial pathway-mediated apoptosis and cell cycle arrest. Our data may suggest that manna could have the potential to exert chemo-preventive effects for the intestine.